Modernizing industrial equipment: a case study of retrofitting a vertical lathe - Siqueira, Carlos Eduardo Batista; Santos, Julio Cesar; Goussain, Blaha Gregory Correia dos Santos [UNESP]; Richetto, Marco Rogério da Silva [UNESP] (Springer Nature, 2024)
The advancement of industrial plants driven by the integration of Industry 4.0 technologies necessitates the modernization of operational machinery, even when such equipment remains in functional condition, to ensure seamless communication across the entire manufacturing process. Moreover, it is crucial to connect these control mechanisms to the centralized plant management system to enhance operational efficiency. This article presents a case study focused on the enhancement of a vertical lathe within an automotive component manufacturing environment. The entire modernization process was systematically executed using high-quality tools, with the implementation of the Plan-Do-Check-Act (PDCA) methodology, which proved instrumental in providing real-time management throughout the upgrade process. Additionally, the Single-Minute Exchange of Die (SMED) technique was employed to optimize the machine’s setup phase, enabling more rapid tool changes. The results of this study highlight the substantial benefits of retrofitting machinery, demonstrating significant improvements in various quality and productivity indicators.
Keywords: Industry 4.0; Modernization; Overall Equipment Efficiency; Retrofitting; Single-Minute Exchange of Die